MUTUAL DEPENDENCE BETWEEN QUALITY MANAGEMENT, KNOWLEDGE MANAGEMENT AND INNOVATION PERFORMANCE - VULTUR, PETRONELA GABRIEL (Ecoforum Journal, 2022)
Abstract From ancient times, wealth and power have been associated with the possession of physical resources. The traditional factors of material, human, monetary production were predominant of a physical nature. Therefore, the need for knowledge was limited. The industrial revolution of past centuries was predominantly based on human physical strength and money capital. A significantly different situation is foreseen for the future. Wealth and power in the 21st century will come primarily from intangible intellectual resources, from the capital of knowledge. The knowledge revolution therefore consists precisely in this transition from the economy dominated by physical, tangible resources, to the economy dominated by knowledge. The process is particularly comprehensive and profound, generating essential changes in all components of economic activities, analogous to those produced by the industrial revolution. We are currently in the early stages of the knowledge revolution. Products and services are more knowledge intensive. Due to this, the delimitation between products and services is becoming more and more difficult. Knowledge tends to become the main feature of activities, more than the resulting products or services. The impact of the knowledge revolution becomes visible in the volatility of the market, the uncertainties regarding the direction of economic activities, the job insecurity felt by people.